Currency misalignments and exchange rate regimes in Latin American countries: a trade-off issue - Carrera, Jorge (2020)
This paper conducts an in-depth empirical investigation on the impact of the exchange rate regime (ERR) on real currency misalignments in a panel of 17 Latin American countries over the 1970-2016 period. We consider explicitly the two dimensions of misalignments, size and persistence, and evaluate four different ERR classifications. We also pay attention to cross-sectional dependencies across countries that appear to be important in Latin America, and provide several robustness checks. Our main findings show that, although fixed ERR perform well in limiting the size of misalignments --and in reducing inflation and fiscal deficit-- the disequilibria are more persistent. On the contrary, allowing for more flexibility reduces persistence but increases the size of misalignments. Overall, we show that Latin American countries face a crucial trade-off when they have to choose their ERR.